Domestication and feedback: bidirectional hijacking in pancreatic ductal adenocarcinoma microenvironment - Yuxi Qiao; Haobo Yin; Yong Zhang; Jingdong Zhang; Qian Dong (Frontiers in Immunology)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by a tumor microenvironment (TME) composed of a dense extracellular matrix, cancer-associated fibroblasts (CAFs), vasculature, neural elements, and immune cell populations. This complex network promotes tumor proliferation, invasion, metastasis, and resistance to immunotherapy and chemotherapy. The microenvironmental characteristics of the various PDAC subtypes are discussed in this review. And we examines the role of cancer cells in the TME, highlighting their ability to manipulate stromal components to serve as collaborators in tumor progression. Furthermore, we explored the formation mechanism of the immunosuppressive microenvironment in PDAC, paying attention on Inflammation and intrinsic genetic alterations, the regulatory effect of metabolic reprogramming, the contribution of CAFs and the role of immune cells in cancer cell metastasis. This review shows the role of soluble molecules and exosomes in facilitating PDAC progression and immune evasion within the microenvironment. In conclusion, we outline the novel therapeutic strategies that focus on the interaction between cancer cells and their microenvironment, with the objective of offering new insights for future precision medical interventions.